Manufacturing bio-bricks using microbial induced calcium carbonate precipitation and human urine - Lambert, Suzanne (Department of Civil Engineering, 2020)
The production of building materials is a significant contributor to anthropogenic greenhouse gas emissions with conventional kiln brick production being one of the most energy intensive processes. In addition, phosphorus is a resource that is required by all living organisms and is a key ingredient in many fertilisers. The demand for building materials and global natural phosphate rock (phosphorous) are increasing and decreasing respectively as urbanization increases. Naturally occurring phosphorous is expected to experience a peak in the near future after which it will be completely depleted. Urine has been identified as a potential source of phosphorous for fertiliser production as well as urea for microbial induced calcium carbonate precipitation (MICP) applications. MICP is a natural process that has the ability to produce bio-building material. Urine accounts for a small percentage of the total volume of domestic wastewater but contains a large percentage of the nutrients wastewater treatment plants (WWTP) seek to remove before they adversely affect receiving water bodies. The unprecedented rate of climate change and the associated pressures, coupled with the increased awareness around the depletion of natural resources, presents a significant challenge for which innovative and sustainable solutions are required. The reason for engaging in this project was to investigate if the urea present in human urine could be used in the natural MICP for the production of bio-bricks while at the same time recovering phosphorus from urine. Firstly, a thorough review of literature was conducted to assess current innovations pertaining to the dissertation topic. The process of bio-brick production by MICP requires a urea rich solution which could be recovered from urine. However, the urea present in urine naturally degrades and this process needs to be delayed if urine is to be used as a urea source for MICP. This was achieved by “stabilising” the urine with calcium hydroxide. Sporosarcina pasteurii (S. pasteurii) was the bacteria strain used to help drive the MICP process. The bacteria degraded the urea present in the urine to form carbonate ions which then combined with the calcium ions present in the urine solution to produce calcium carbonate. This calcium carbonate was then used as a bio-cement to glue loose sand particles together in the shape of a brick. The cementation media was made by adding calcium chloride and nutrient broth to the stabilised urine, and lowering its pH to 11.2. The purpose of adding calcium chloride was to improve the efficiency of the process since the stabilised urine did not have enough calcium ions. Ordinary sand mixed with Greywacke aggregate and inoculated with S. pasteurii bacteria was used as the media for the MICP process. Bio-brick moulds were filled with the sand mixture and sealed. The cementation media was pumped through the bio-brick mould to fill its’ pore volume. The media was retained in the moulds for a defined retention time ranging from 1-8 hours. At the end of every retention time, new cementation media was pumped through the bio-brick to fill it’s pore volume again. iv To establish an optimal starting influent calcium concentration the influent calcium concentration changed between experiments. Additionally, in subsequent experiments, the calcium concentration was raised in a stepwise manner during an experiment to establish the maximum amount the influent calcium concentration could be raised to before the microbial community experienced adverse effects. Additionally, experiments explored the effects a range of retention times had on the bio-brick system in order to establish an optimal retention time. Another experiment was set up to investigate the relationship between the number of treatments and the resultant compressive strength. The findings from the above-mentioned experiments further guided subsequent experiments which singled out and tested certain factors thought to be affecting the bio-brick system. The factors tested include after treatment washing, ionic strength, pH and calcium concentration of the influent cementation media. Possible alternative nutrient medias (ANMs) were also investigated for a cheaper alternative to the laboratory grade growth media used to grow the bacteria. Lastly, an integrated system that produced both fertilisers and bio-bricks was developed. Its basic economics of raw material inputs and outputs were used to assess the financial implications of the proposed system, and the social and policy barriers likely to affect the implementation of an integrated urine treatment system were examined. Urine treated with calcium hydroxide offers a urea-rich solution that can be used for MICP processes. This resulted in the worlds’ first bio-brick “grown” from human urine. The starting influent calcium concentration reached a maximum of 0.09 M before adverse effects to the microbial community were experienced. Furthermore, in terms of a stepwise increase during the treatment cycle, the influent calcium concentration could be raised to 0.12 M without any adverse bacteria effects. The minimum retention time the bio-brick system could withstand was 2 hours which allowed the treatment cycle to be completed in a shorter time. The highest compressive strength obtained was equal to 2.7 MPa. To produce this strength about 31.2 L of stabilised urine was used. The relationship between the number of treatments and the compressive strength showed that an increase in the number of treatments increased the compressive strength. Both the pH and ionic strength of the urine were identified to have an inhibiting effect on the ureolytic activity and MICP process. Additionally, using an influent cementation media with an optimal pH for urea hydrolysis, improved the bacteria’s ability to operate at higher ionic strengths. However, when the stabilised urine was stored, urea hydrolysis occurred earlier likely because of external contamination by naturally occurring bacteria in the lab. LML (Lactose mother liquor) was identified as alternative growth media for S. pasteurii growth which could reduce raw material costs considerably. The bio-brick production process was found to be more cost-effective if it was incorporated into the integrated urine treatment process system. The integrated system included fertiliser production by recovering calcium phosphate fertilisers and ammonium sulphate fertilisers before and after the bio-brick production respectively. Producing 1000 bio-bricks a day would require 23% of Cape Towns’ population daily urine production and would incur a profit of ZAR 7330 per day between the raw material cost and the revenue from sales. For implementation in a South African context, certain policy barriers need to be overcome. Potential paths for implementation are reclassifying the urine for its use in an industrial process and obtaining an operating permit or seeking an exemption for a permit through the ECA (Environment Conservation Act). Research suggests that products from the integrated system are likely to be socially v accepted and that a combined appeal to people's environmental sensitivities and targeted marketing messages would enhance people’s acceptance. Finally, recommendations for further paths to take to build on the research established in this dissertation were made. It is recommended that additional characteristics of the bio-bricks should be tested, recycled material should be used as media for bio-bricks, the bacteria strain should be modified and methods for reducing the ionic strength of urine should be investigated. Additionally, it is recommended that consumers’ willingness to use urine-based products should be further studied, the legislative options for implementing bio-brick and fertiliser production should be investigated and a more detailed and expansive economic analysis should be performed.